A Pragmatic and Discourse Analysis of Newspaper Headlines in English and Uzbek - Ismatullayeva Nigora Muhammadali qizi; Shakirova Madina Bahriddinovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article provides information on the news presented in newspapers and the pragmatic analysis of the news in them and their presentation in English-Uzbek translations.Today, the text of newspaper headlines has become the main subject of scientific research in linguistics, psychology, sociology, journalism, pragmatics and several humanities.